The genus Deschampsia and the epithet “ alpina” - Jorge O. Chiapella (Universidad Nacional del Comahue); Zhi-Qing Xue (University of Vienna); Josef Greimler (University of Vienna) (PhytoKeys, 2021)
The abstract is available here: https://uscholar.univie.ac.at/o:1603126 The abstract is available here: https://uscholar.univie.ac.at/o:1603126